Production of metal cord construction size 7 x 7 x 0,22 on root machines type RIR –15 - O. M. Matveev; V. V. Shapovalov; I. V. Muzychenko; O. A. Starkina (Литьë и металлургия, 2020)
Since the appearance of the reinforcing material for automobile tires and rubber products, such as metal cord, you can observe its constant development. Tougher competition among the tire manufacturers makes it a priority to develop new and unique types of these products with improved technical characteristics. The article describes the development trend in the production of metal cord for large and super – large tires in Belarus since 2007 and up to the present.The purpose of this project is to ensure the delivery of large – diameter metal cord to Belshina OJSC in the required volume. The solution to the problem of fulfilling the volume of deliveries of metal cord with a limited number of equipment while maintaining the quality of products is considered. In the process of work, an alternative scheme for manufacturing metal cord was developed, the selection of technological parameters for tuning and twisting was carried out, and the rope equipment was modernized.